Sophora alopecuroide - Taraxacum decoction (STD) inhibits non-small cell lung cancer via inducing ferroptosis and modulating tumor immune microenvironment - Ouyang Xiaohu; Jingbo Wang; Xiaoyuan Qiu; Shuxin Song; Junyi Li; Shanshan Luo; Qianyun Chen; Desheng Hu (Heliyon)
The Sophora alopecuroide - Taraxacum Decoction (STD) is a traditional Chinese herbal formulation that has demonstrated significant potential in combating tumors. Despite its apparent effectiveness, the specific mechanisms through which STD exerts its anti-tumor properties remain largely unexplored and are yet to be fully understood. In our study, we provided evidence that STD effectively inhibits cellular growth and movement, as well as halting the cell cycle at the G2/M checkpoint. Furthermore, our pharmacological network analysis indicated that STD might induce cell death through a process known as ferroptosis. This hypothesis was substantiated by observing important biochemical changes associated with ferroptosis, including a decrease in glutathione (GSH) levels, an increase in iron accumulation, and elevated levels of reactive oxygen species (ROS) and lipid peroxidation. Additionally, we noted a significant rise in the expression of pro-ferroptosis genes such as Keap1, Nrf2, and HO-1, further supporting our findings. Significantly, and in line with the in vitro results, STD also showed a strong ability to inhibit tumor growth by inducing ferroptosis in a subcutaneous tumor model. Additionally, STD treatment changed the tumor immune microenvironment (TIME), as seen by an increase in CD107a+ CD8 and NK cells within the tumor. These findings demonstrate that STD induces ferroptosis and alters TIME to combat tumors, suggesting that STD may be a viable alternative treatment for patients with NSCLC.